Verifing the Accuracy of a New Scale of Parental Burnout - Kwiatkowski, Piotr; Sekułowicz, Małgorzata (Przegląd Badań Edukacyjnych (Educational Studies Review), 2016)
The article presents results of a research on the accuracy of a new tool dedicated to measure the burnout level among parents of children with disabilities. The tool’s construction is based on transactional and resources concept of stress and burnout. It was necessary to determine a correlation between the burnout level and individual ability of the parent to positively adapt and their strategies for coping. As one can expect, the burnout level is related to the sense of coherence and two different resilience values. The article also points out two essential links between the burnout and the coping strategies. Parents suffering from burnout are less likely to use strategies focused on solving problems and more prone to use defense strategies. The results introduced in the article permit us judge the accuracy of the research tool positively.